Approach to evaluation of fever in ambulatory cancer patients receiving chemotherapy: A systematic review. (December 2016) - Krzyzanowska, M.K.; Walker-Dilks, C.; Morris, A.M.; Gupta, R.; Halligan, R.; Kouroukis, C.T.; McCann, K.; Atzema, C.L.
Highlights: Fever is common in cancer patients receiving chemotherapy in the outpatient setting. The approach to evaluation of fever in such patients is not standardized. Limited evidence is available to guide the assessment of fever in ambulatory cancer patients. Most research focuses on patients already diagnosed with febrile neutropenia. Prospective studies of risk stratification algorithms are needed to define the best model of care. Abstract: Purpose: To define the optimal model of care for patients receiving outpatient chemotherapy who experience a fever. Fever is a common symptom in patients receiving chemotherapy, but the approach to evaluation of fever is not standardized. Methods: We conducted a search for existing guidelines and a systematic review of the primary literature from database inception to November 2015. Full-text reports and conference abstracts were considered for inclusion. The search focused on the following topics: the relationship between temperature and poor outcome; predictors for the development of febrile neutropenia (FN); the timing, location, and personnel involved in fever assessment; and the provision of information to patients receiving chemotherapy. Results: Eight guidelines and 38 studies were included. None of the guidelines were directly relevant to the target population because they dealt primarily with the management of FN after diagnosis. The primary studies tended to include fever as one of many symptoms assessed in the setting of chemotherapy. Temperature level was a weak predictor of poor outcomes. We did not find validated prediction models for identifying patients at risk of FN among patients receiving chemotherapy. Several studies presented approaches to symptom management that included fever among the symptoms, but results were not mature enough to merit widespread adoption. Conclusion: Despite the frequency and risks of fever in the setting of chemotherapy, there is limited evidence to define who needs urgent assessment, where the assessment should be performed, and how quickly. Future research in this area is greatly needed to inform new models of care.